Relação entre esplenectomia e reprodução em camundongos - Dalton Muniz Santos (2014)
INTRODUCTION: The spleen is an important organ which plays a role in blood clearance, haematopoiesis, metabolism, and immune responses to different antigens, in addition to storing and controlling the release of metals, aminoacids and the organism defence elements. This organ may be involved in a wide range of disturbances, and is frequently injured in abdominal traumas, which is most commonly treated by splenectomy. To avoid the severe repercussions of asplenia, the spleen has been preserved by means of conservative procedures, including partial or subtotal splenectomies, or autogenous splenic tissue implants. Some accounts point to sexual inactivity as being among the adverse effects of splenectomy; however, no study to date has be able to produce evidence which reflects the relationship between the spleen and sexual activity. OBJECTIVE: To verify the effect of splenectomy on reproduction. METHOD: The present study analysed 25 pairs of mice, divided into five groups: Group 1: control without surgery; Group 2: control of those subjected to laparotomy and laparorrhaphy; Group 3: splenectomy in male mice; Group 4: splenectomy in female mice; Group 5: splenectomy in male and female mice. In addition, 20 Holtzman rats were divided into two groups: Group 6: control without surgery and Group 7: splenectomy. The mice were studied according to both the number of pregnancies and the number of pups per pregnancy. In the two rat groups, the testosterone levels were dosed. In the mouse groups, reproduction after surgical interventions, the number of pups in each group and the time between pregnancies were assessed. RESULTS: A reduction in the number of pregnancies, as well as in the number of pups, could be observed in splenectomised male mice that had been coupled with normal female mice. In the rats groups, an increase in testosterone could be identified after splenectomy. CONCLUSION: A reduction in the number of pregnancies and in the number of pups could be observed in splenectomised males that had been coupled with normal female mice. Splenectomy is associated with an increase in serum testosterone levels in rats.